(untitled) (Web of Teachers: Inderscience Research, 2024)
Affixes that are added to the base to create a new meaning are called word-forming affixes. They have the property of forming nouns, adjectives, verbs, and adverbs within independent word classes. The word-forming affixes belonging to these word classes undergo certain changes when they are added to the base.